Banks' net interest margin and the level of interest rates - Ramona Busch; Christoph Memmel (Deutsche Bundesbank, 2015)
An increase in the level of interest rates is said to have a negative impact on banks' net interest margins in the short run. Using a time series of more than 40 years for the German banking system, we show that the opposite effect exists in the long run, where an increase in the level of interest rates by 100 basis points leads to an estimated increase of 7 basis points in the banks' net interest margin. In addition, we analyze the consequences of the low-interest rate environment and find that banks' interest margins for retail deposits, especially for term deposits, have declined by up to 97 basis points.
Keywords: G21; 330; net interest margin; level of interest rates